Technological Acceptance Model (TAM) in higher education: A Systematic Literature Review - Robles, Elaine (2024)
This article focuses on models of technological acceptance in university education and aims to identify the factors that have added to the original model and allowed its continuity over the years. Giving a broader picture of the use of adoption models at the university level. Therefore, a systematic review of the literature was conducted, using a methodology based on three stages: planning, development and results; the period covered was between the years 2013 to 2023. The results section presents the selected articles, which were obtained from the search of the databases: Frontiers, Science Direct, Taylor & Francis, Ebsco and Emerald. A total of 19295 potential articles were identified and, applying the criteria, 61 articles were chosen for this research. An analysis of the articles was performed to answer the research questions. Finally, the conclusions of the study are presented.